Pengaruh Harga Dan Karakteristik Kewirausahaan Terhadap Kepuasan Pelanggan (Studi Kasus Pada Pengunjung Mang One): - Amelia, Riska; Dahmiri, Dahmiri; Kurniawan, Dwi (Jurnal Dinamika Manajemen, 2024)
The purpose of the study was to determine the effect of price and entrepreneurial characteristics on customer satisfaction (case study on mang one visitors). The object of this research is mang one visitors. In this study, the sample size was taken using the lemeshow formula totaling 97 people who came from mang one customers. The approach used in this research is a quantitative descriptive approach. The sampling technique in this study was observation, literature study method and questionnaire. This study uses multiple linear regression analysis techniques with the help of the SPSS version 26 program. The results of the statement questionnaire were tested using validity and reliability tests which showed the data was valid and reliable. The results of this study indicate that the price variable (X1) and entrepreneurial characteristics (X2) have a simultaneous effect of partially on mang one customer satisfaction.